Experimental studies on the effects of sheet resistance and wettability of catalyst layer on electro-catalytic activities for oxygen evolution reaction in proton exchange membrane electrolysis cells. (16th October 2020) - Mo, Jingke; Yang, Gaoqiang; Li, Yifan; Kang, Zhenye; Bender, Guido; Pivovar, Bryan S.; Green, Johney B.; Zhang, Feng-Yuan
Abstract: As the most important part of electrochemical reaction in proton exchange membrane electrolysis cells (PEMECs) for water splitting, oxygen evolution reaction (OER) occurs at the anode catalyst layer (CL). The distribution of the OER site is affected by many factors, such as properties of CL, operation parameters, procedures, etc. To study the effects of properties of CLs on the distribution of OER site on the CL, and consequently affect the performance of PEMECs, CLs with different sheet resistances are tested under different operation conditions. The phenomena of OER on CLs are captured by a high-speed and micro-scale visualization system in-situ and analysed coupled with electrochemical results. The results show that both sheet resistance and wettability of CLs have significant impact on the distribution of the OER site, which can help optimize the design of membrane electrode assembly and improve the operating parameters for electrochemical devices. Highlights: Oxygen bubble generation and dynamics are captured in-situ and analysed in PEM ECs with different properties of anode CL. The sheet resistance of anode CL has a significant impact on the distribution of oxygen bubble generation site. The wettability of anode CL with PtB as catalyst changes along with the conditioning time. The wettability of anode CL affects the distribution of oxygen bubble generation site and the performance of PEM ECs.